Refugee Crossroads in Africa - Szilágyi, Béla (Journal of Central and Eastern European African Studies, 2025)
There are several refugee crossroads in Africa. One of the most significant and most recent is in the Sahel, where refugees from Sudan, Central African Republic, and Cameroon flee to the country of Chad. This paper examines the humanitarian and forced migration situation of the country with a crisis that affects at least 3.9 million people. The research analyzes humanitarian organisations’ dual approach to humanitarian assistance and development projects, particularly focusing on refugee support and capacity building in healthcare and education sectors. Through qualitative assessment of multiple intervention sites, including the Kalambari and Guilmey refugee camps, the study documents sustainable solutions in vocational training, healthcare delivery, and infrastructure development. More specifically, the assessment of multiple intervention sites demonstrates a Hungarian humanitarian aid and development organization, Hungarian Baptist Aid’s impact through establishment of optical centers in N’Djamena and Moundou hospitals; delivery of specialized training for 40 IT professionals; implementation of sustainable sewing programs across four locations; and infrastructure development including solar energy systems at Guinebor 2 Hospital serving 172,000 people. The study documents critical operational challenges in Chad’s complex environment, where only 22 percent of rural births receive qualified medical assistance, and telecommunications infrastructure remains severely limited with 0.68 mobile connections per person. Key findings demonstrate the necessity and effectiveness of integrated programming that simultaneously serves refugee and host communities while building local capacity through sustainable infrastructure and skills development, exemplified by successful sewing training programs and vision care initiatives. The research identifies critical operational challenges, including bureaucratic challenges, security concerns, and infrastructure limitations, while highlighting the importance of strategic partnerships with local authorities and international organizations for project sustainability. This analysis provides evidence-based insights for NGOs operating in the Sahel region, highlighting the correlation between security protocols and aid worker safety in conflict zones, noting that 33 percent of international staff incidents occur within the first three months of deployment. The findings underscore the necessity of comprehensive risk assessment, cultural sensitivity, and sustainable project design in humanitarian operations within the Sahel region.